Post-Secondary Education and Information on Labor Market Prospects: A Randomized Field Experiment - Sari Pekkala Kerr; Tuomas Pekkarinen; Matti Sarvimäki; Roope Uusitalo (Institute for the Study of Labor (IZA), 2015)
We examine the impact of an information intervention offered to 97 randomly chosen high schools in Finland. Graduating students in treatment schools were surveyed and given information on the labor market prospects associated with detailed post-secondary programs. A third of the students report that the intervention led them to update their beliefs. Experimental estimates suggest that it also affected the application behavior of the least informed students. However, this group of affected students is not sufficiently large for the intervention to have an average impact on applications or enrollment.
Keywords: J24; I23; 330; education; information; earnings; randomized field experiments